2020
DOI: 10.9734/cjast/2020/v39i3631077
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment on Knowledge of Weather Based Agro-advisory Services among Farmers in Tiruvallur District, Tamil Nadu

Abstract: Weather influences the production and productivity of various crops. If farmers aware about           the real time weather factors such as temperature, relative humidity, wind speed, wind           direction and rainfall it will be the effective to prevent the crop failure and achieve high yield with better economic returns. The right weather information at right time facilitates the farmers to plan agricultural operations from selection of crops to post harvest to avoid crop losses. 382 AAS bulletins were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
2
4
0
Order By: Relevance
“…About 69.20 percent of farmers found AAS useful for planning harvesting and threshing operations.59.20 percent of farmers used AAS for managing their insect and pest, 45.20 percent found it useful for timely and optimum use of fertilizer. About 40.30 percent of farmers check weather forecast for scheduling irrigation and 39.10 percent for post harvest operations.These results are in conformity with studies reported by Prasadet al,(2020)[11] .…”
supporting
confidence: 94%
“…About 69.20 percent of farmers found AAS useful for planning harvesting and threshing operations.59.20 percent of farmers used AAS for managing their insect and pest, 45.20 percent found it useful for timely and optimum use of fertilizer. About 40.30 percent of farmers check weather forecast for scheduling irrigation and 39.10 percent for post harvest operations.These results are in conformity with studies reported by Prasadet al,(2020)[11] .…”
supporting
confidence: 94%
“…This may facilitate the farmers to determine the farming operations like sowing, irrigation, fertilizer and pesticide application. Similar results were reported in the impact study conducted in Tiruvallur, Tamil Nadu [10] which will be performed or postponed."…”
Section: Preference Of Mode Of Technology Disseminationsupporting
confidence: 81%
“…Farmers can save on input costs such as fertilizers, pesticides, and water by following the recommendations provided in the advisories. This can lead to reduced waste and increased costeffectiveness in farming practices (Prasad et al, 2020) [5] .…”
Section: Cost Savingsmentioning
confidence: 99%